2014
DOI: 10.1177/0022343314551081
|View full text |Cite
|
Sign up to set email alerts
|

Not all dictators are equal

Abstract: Since the end of the Cold War, Western powers have frequently used sanctions to fight declining levels of democracy and human rights violations abroad. However, some of the world’s most repressive autocracies have never been subjected to sanctions, while other more competitive authoritarian regimes have been exposed to repeated sanction episodes. In this article, we concentrate on the cost–benefit analysis of Western senders that issue democratic sanctions, those which aim to instigate democratization, against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Anticipating fraud and vulnerability in regional head elections in this study, it was found that the tendency of incumbent candidates was not neutral (Marsallindo & Safitri, 2021;Thawnghmung, 2016;Von Soest & Wahman, 2015) in utilizing their power in influencing voters who have influence. strong against bureaucracy.…”
Section: Introductionmentioning
confidence: 73%
“…Anticipating fraud and vulnerability in regional head elections in this study, it was found that the tendency of incumbent candidates was not neutral (Marsallindo & Safitri, 2021;Thawnghmung, 2016;Von Soest & Wahman, 2015) in utilizing their power in influencing voters who have influence. strong against bureaucracy.…”
Section: Introductionmentioning
confidence: 73%
“…Economic preponderance raises the RIO leader's sanctioning capability and thus its credibility because the more preponderant the leader, the greater its ability to cause economic hardships in target countries while minimizing harm to its own economy. Maximizing harm to the target and minimizing harm to the sender is at the heart of successful sanctions (von Soest & Wahman, 2014). In short, the economic weight of the RIO leader makes its anti-coup commitment credible, and the pre-coup expected costs of its sanctions to the target country high without actually undertaking sanctions.…”
Section: Rio Leaders and Domestic Political Stabilitymentioning
confidence: 99%